The international law of sovereign debt dispute settlement - Nakajima, Kei, 1983- (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2022)
The first two decades of the twenty-first century witnessed a series of large-scale sovereign defaults and debt restructurings, in which sovereigns struggled to negotiate with recalcitrant bondholders, particularly hedge funds. Also, the outbreak of the COVID-19 pandemic in 2020 heralded a bleak financial outlook for many developing and emerging market countries, requiring sovereign debt restructuring in times of great macroeconomic uncertainty. Given the absence of a multilateral mechanism for sovereign debt restructuring equivalent to domestic corporate bankruptcy system, however, defaulted sovereigns often suffer from holdout litigation wrought by bondholders. This book proposes ways in which such legal actions could be regulated without the undue expense of bondholders' remedies by exploring the mechanism of balancing bondholder protection and respect for sovereign debt restructuring at various stages of litigation and arbitration proceedings.
Setting the scene -- The emerging framework for sovereign debt discourse -- Sovereign immunities and other statutory mechanisms -- Collective Action Clauses (CACs) : contractual regulation of holdout litigation -- The Pari Passu Clause : regulating holdouts through injunctive relief -- Jurisdiction of arbitral tribunals over sovereign debt disputes -- Admissibility of sovereign bond claims : mass claims arbitration as a supplemental leverage over holdouts -- Checks and balances at the stage of merits.
Title from publisher's bibliographic system (viewed on 27 Sep 2022).
Keywords: Debts, Public -- Law and legislation; Debts, External -- Law and legislation; Arbitration (International law); Default (Finance) -- Law and legislation; Debt relief; Dispute resolution (Law)